New coronavirus infection (COVID-19) and major rheumatic diseases - Dmitry I. Trukhan; Inna A. Viktorova (LLC "MEDIAFORMAT", 2023)
The main target of the novel coronavirus infection (COVID-19), spread by the SARS-CoV-2 virus, is the respiratory system. However, as data on COVID-19 accumulates, it is becoming increasingly clear that there is a complex interaction between the virus and the immune system, ranging from mild and controlled responses to severe and dysfunctional multitissue targeted autoimmune responses. A literature search was conducted on the association of major rheumatic diseases with the new coronavirus infection COVID-19 in the electronic search engines PubMed, Scopus, eLIBRARY. The literature sources found indicate that the new coronavirus infection COVID-19 certainly has a specific effect on the musculoskeletal system in general, and in particular on individual rheumatic diseases. In a number of studies, the theoretical prerequisites for an association between major rheumatic diseases and COVID-19 have received clinical confirmation.